Expression of botulinum toxin binding sites in Xenopus oocytes. - Bakry, N M (1997)
The binding of iodinated botulinum toxin type B to nerve membranes was studied by using rat and mouse preparations. The toxin was examined both in the single-chain and in the proteolytically processed dichain form, and binding sites both in the spinal cord and in various brain regions were assayed. Rat and mouse brains possessed specific binding sites for botulinum toxin type B. The average Kd values for the various rat and mouse membrane preparations examined were 4.2 +/- 0.7 nM and 3.7 +/- 0.9 nM, respectively. The average Bmax values for the same tissue preparations were 7.3 +/- 0.7 pmol/mg of protein and 7.5 +/- 1.9 pmol/mg protein, respectively. The binding of botulinum toxin type B to rat brain membranes was not antagonized by a polyclonal antibody against the cytosolic domain of synaptotagmin 1 or by a monoclonal antibody directed against the luminal domain of synaptotagmin 1. In addition, these antibodies did not protect the mouse phrenic nerve-hemidiaphragm from toxin-induced neuromuscular blockade. Extraction of whole-brain mRNA and injection into Xenopus oocytes led to expression of binding sites for botulinum toxin. Extraction and injection of cerebellar mRNA led to expression of a higher density of binding sites. The number of binding sites was not diminished when oocytes were pretreated with antibodies against the cytosolic and luminal domains of synaptotagmin 1. These findings are likely to aid in the isolation, characterization, and reconstitution of toxin binding sites.